In Hawthorne's shadow : American romance from Melville to Mailer - Coale, Samuel (University Press of Kentucky, 1985)
""The world is so sad and solemn, "" wrote Nathaniel Hawthorne, ""that things meant in jest are liable, by an overwhelming influence, to become dreadful earnest; gaily dressed fantasies turning to ghostly and black-clad images of themselves."" From the radical dualism of Hawthorne's vision, Samuel Coale argues, springs a continuing tradition in the American novel. In Hawthorne's Shadow is the first critical study to describe precisely the formal shape of Hawthorne's psychological romance and to explore his themes and images in relation to such contemporary writers as John Cheever, Norman Mailer